Lead-Zinc Smelting - 40 Years of Pollution Control - G. R. McMeekin (Canadian Institute of Mining, Metallurgy and Petroleum, 1972)
"THE TOPIC suggested for my contribution to this Symposium was ""Lead-Zinc Smelting - 40 Years of Pollution Control"". The history of the development of smelting industry at Trail and the control of sulphur dioxide could make quite an interesting historical study. However, in the field of environmental control, the public is not particularly interested in what you did yesterday, but rather what you are doing today and what you are planning to do tomorrow. I can't fault this approach, but because there are some subject lessons that history can demonstrate, I would like to tell enough of the story (under three headings) to bring a focus on matters of contemporary concern in regard to public relations and ecology. The three general headings suggested are: (1) time before the capture of by-product sulphur; (2) the capture of sulphur; and (3) the ecological and public relations conclusions from these."